PARENTING PATTERNS ON CHILD SOCIAL-EMOTIONAL DEVELOPMENT DURING PANDEMIC COVID-19 - Umianita Risca Wulandari; Dian Kumalasari (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2021)
The age of the child is the best period to shape and develop a child's' potential. During the Covid-19 pandemic, it was difficult for most children to meet their social needs. So, the parents must accompany and care for their children, so their needs are met. This study aimed to determine the relationship between parenting styles and children's social-emotional development during the Covid 19 pandemic. This study was a quantitative study using a cross-sectional design. The sampling technique used was purposive sampling and obtained 40 mothers who have pre-school age children. The data were analyzed using the Chi-Square test. The results showed that the number of respondents with sufficient parenting styles with children who had good social-emotional development was 31 people. Meanwhile, respondents who had a good parenting style with good social-emotional development were three people. Chi-square analysis showed a p-value of 0.154, which means there was no significant relationship between parenting style with children's social-emotional development. Other factors probably affect children's social-emotional. Therefore, further study is needed, such as environmental conditions, the fulfillment of recreational needs, and the school environment. Keyword: parenting patterns, social-emosional, children